2019
DOI: 10.1186/s40468-019-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

English language teaching in Bangladesh today: Issues, outcomes and implications

Abstract: Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 45 publications
4
67
1
Order By: Relevance
“…These interconnections crossing borders have shaped agendas, skill estimates and occupations. In the field of education, subjects covered in basic and higher education are directly affected by primary skills to be developed; for instance, giving priority to science and mathematics, or harmonizing creativity with arts to encourage innovation (OECD, 2013;Rahman et al, 2019) . Trade and R&D among nations along with a knowledge-intensive economy have resulted in the 21st-century skills that must be possessed by the youth.…”
Section: Skills For the Future Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These interconnections crossing borders have shaped agendas, skill estimates and occupations. In the field of education, subjects covered in basic and higher education are directly affected by primary skills to be developed; for instance, giving priority to science and mathematics, or harmonizing creativity with arts to encourage innovation (OECD, 2013;Rahman et al, 2019) . Trade and R&D among nations along with a knowledge-intensive economy have resulted in the 21st-century skills that must be possessed by the youth.…”
Section: Skills For the Future Of Workmentioning
confidence: 99%
“…In general education, there are Private schools and Public schools. Most of the private schools' medium of instruction is English (Sommers, 2011;Chowdhury and Kabir, 2014;Rahman et al, 2019). English medium schools are accredited by NEASC, CoIS, IGCSE, Edexcel and CIE, and mostly located in big cities (97,96% in total 147 schools).…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh is a monolingual country of 160 million people and of the total population, 98% people use Bangla as their first language. This predominately-monolingual identity of the nation is emphasized in its nationalist discourses (Rahman et al, 2019). Hence, it is quite challenging to practice CLT exclusively in language teaching classrooms as both students and teachers are highly interested in using Bangla as their medium of communication, and the overuse of their own language means that they will have less chance to learn English (Harmer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of Bangladesh, changing an entire curriculum all of a sudden to dispatch knowledge about other disciplines along with sharpening language skill might be difficult, but it demands future research and evaluation as English possesses a vast space in the curriculum. If properly analyzed, it is found that the socio-cultural history of English, in Indian subcontinent, encroaching on the national curriculum of the country has "their roots in the colonial past" with the use of English "in political discourse" "to communicate with the elites of the region" (Rahman et al, 2019). Following the integration of English into national curriculum, "during the Pakistani regime, English continued to be widely used as a recognized state language with the status of second language" in earlier East Pakistan, present Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…After independence, Bangladesh adopted "article 3" in "1972" that legalized "the use of English in the official, social and educational spectrums" of the country. Such a long history of English gradually entering the social, cultural and academic domain in Bangladesh eventually necessitates the importance of design, implementation and investment regarding the training and use of English (Rahman et al, 2019). "With over 30 million students learning English as a compulsory subject from grade 1 in the different streams of pre-tertiary education, Bangladesh has one of the largest English learning populations in the world", according to M. Obaidul Hamid and Elizabeth J. Erling (2016).…”
Section: Introductionmentioning
confidence: 99%